Clay surfaces : fundamentals and applications - Wypych, Fernando; Satyanarayana, Kestur Gundappa (Interface science and technology, 2004)
Clay plays an important role in everyday life. This versatile mineral is used in housing, improving the environment as a waste treatment material and also in biological applications and medical health care. Clay Surfaces contains 17 chapters which deal with various aspects of natural and man made (synthetic) clay. Well written by experts in both experimental and theoretical areas, this book takes the reader into the fascinating world of the chemistry and physics of clay mineral surfaces and interfaces as well as the complex phenomena on the surfaces involved in clay related systems. This book.